Autobiography and natural science in the age of Romanticism - Kuhn, Bernhard Helmut (Ashgate, 2009)
The nature of identity and the identity of nature – Natural science and the self in Rousseau's Confessions – Reveries and the re-enchantement of nature – Goethe's autobiographical science – Self-formations: order and disorder in poetry and truth – The metamorphosis of Thoreau – Prolific hybrids : Walden and Thoreau's natural history
9780754661665
Keywords: Rousseau; Jean-Jacques; Goethe; Johann Wolfgang von; Thoreau; Henry David; Rousseau; Goethe; Thoreau; Confessions; Rêveries du promeneur solitaire; Aus meinem leben. Dichtung und wahrheit; Walden; Identity (Psychology) in literature; Literature and science; Authors; Autobiography; Natural history in literature; Self in literature; Romanticism; Science and the humanities; Natural history literature